Design with the other 90% : cities - Smith, Cynthia E. (Cooper-Hewitt, National Design Museum, 2011)
Through essays, interviews, and profiles of 60 examples of community-led design, this second book in an ongoing series examines the issues arising from unprecedented urban growth, primarily in the informal settlements of emerging and developing economies, as well as efforts in urban planning, sustainable design, affordable housing, entrepreneurship, nonformal education, communication, food, security, water and sanitation, and public health in these communities.